How accessible are interpreter services to dialysis patients of Non-English Speaking Background? - Zimbudzi, E.; Thompson, Sandra; Terrill, B. (Australasian Medical Journal Pty Ltd, 2010)
Background. Benefits of utilising professional interpreters in clinical settings have been well documented. However, not many studies have focused on use of professional interpreters by dialysis patients of Non-English Speaking Background (NESB) who are in the clinical settings every second day of their lives. The underlying question for this research was to determine the level of interpreter utilisation by dialysis patients of NESB at a major urban teaching hospital. Method. A multi-method approach was used involving (a) in-depth interviews of health care professionals working with dialysis patients to elicit their views regarding interpreter access and use by dialysis patients of NESB, (b) observations of interactions between staff and dialysis patients of NESB and (c) review of medical records belonging to dialysis patients of NESB who were admitted 24 months prior to the study.Results. Interviews revealed that only 50% of Health Care Workers (HCWs) had accessed an interpreter for dialysis patients of NESB over a period of six months. Observations of staff/NESB patient interactions showed that professional interpreters were used in only 25% of the observed occasions. There view of medical records revealed that there was no evidence of interpreter use in 32% of the records belonging to dialysis patients of NESB. The study also showed that non-compliance with dialysis treatment regime was more likely to occur among patients who had limited access to interpreters. Conclusion. The study demonstrated a suboptimal utilisation of interpreter services by dialysis patients of NESB. Several barriers to inaccessibility and underutilisation of professional interpreters were identified. Recommendations to improve communication between HCWs and dialysis patients of NESB are suggested.